Effects of temperature and compost conditions on the biodegradation of degradable polymers - Jung, EJ; Shin, PK; Bae, HK (SPRINGER-VERLAG SINGAPORE PTE LTD, 1999)
The effectiveness of current biodegradation test methods for degradable polymers under controlled composting conditions was studied in regards to the test temperature and compost condition. When biodegradability tests for the natural (starch, cellulose, PHB/HV) and synthetic (PCL, SG, PLA) polymers were conducted at temperature levels of 35 and 55 degrees C with compost cured at ambient temperature, the degradations of cellulose and starch were higher at 35 degrees C because of the priming effect. On the other hand, degradations of other polymers were higher at 55 degrees C. In the biodegradation test at 55 degrees C, compost harvested right after the thermophilic degradation stage showed higher biodegradation activities than the cured compost for both the synthetic aliphatic polyester (SG) and a natural polymer, cellulose. These results suggest that the biodegradation test conducted at 55 degrees C with the compost, harvested right after the thermophilic degradation stage during composting, showed the highest biodegradation activity under controlled composting conditions.